Elimination of restrictive practices from acute adult mental health care services: A qualitative evidence synthesis of the lived experience literature. - S.L. Bennetts; G. Pepin; S. Moylan; R. Carolin; J.J. Lucas (SSM - Mental Health, 2024)
The calls to eliminate restrictive practices (e.g., seclusion and physical restraint) from mental health care services have been gaining momentum over time and have been one of the many issues at the forefront of international mental health care systems. Whilst it is known that restrictive practices are often harmful and traumatic for the mental health service user, there is a lack of synthesis of the factors that are influencing restrictive practices’ ultimate reduction and elimination from the perspective of mental health service users and practitioners. The aim of this research was to conduct a qualitative evidence synthesis of the literature regarding the perceptions and experiences of mental health service users and practitioners about restrictive practices in mental health care services. A systematic search and inclusion strategy identified 44 relevant articles for review. Inductive thematic synthesis resulted in five themes across the articles: (1) Meaning and emotional experience, (2) Re-traumatisation and dehumanisation, (3) Professional competencies and varying experiences, (4) Balancing safety versus care, and (5) Alternatives to restrictive practices. Discussion of these themes highlighted the many layered and often uncomfortable nature of restrictive practices which can pervade mental health facilities across the world.